Role of lattice defects and crystallite morphology in the UV and visible-light-induced photo-catalytic properties of combustion-prepared TiO2 - Deshpande, Aparna; Madras, Giridhar; Gupta, N. M. (Materials Chemistry and Physics, 2011)
The physico-chemical, photo-physical and micro-structural properties responsible for the strikingly different photocatalytic behavior of combustion-prepared TiO2 (c.TiO2) and Degussa P25 (d.TiO2) samples are elucidated in this study. Electron microscopy and selected area electron diffraction micrographs revealed that the two samples exhibited different morphologies. The grains of c.TiO2 were spherical and comprised of 5-6 nm size primary particle. On the other hand, d.TiO2 consisted of large (0.5-3.0 mu m) size and irregular shape aggregates having primary particles of 15-40 nm cross-sectional diameter. The ESR study revealed that the presence of certain defect states in c.TiO2 helped in stabilization of O-. and Ti3+-OH type species during room-temperature UV-irradiation. No such paramagnetic species were however formed over d.TiO2 under similar conditions. C1s and Ti 2p XPS spectra provide evidence for the presence of some lattice vacancies in c.TiO2 and also for the bulk Ti4+ -> Ti3+ conversion during its UV-irradiation. Compared to d.TiO2, c.TiO2 displayed considerably higher activity for discoloration of methyl orange but very poor activity for splitting of water, both under UV and visible light radiations. This is attributed to enhanced surface adsorption of dye molecules over c.TiO2, because of its textural features and also the presence of photo-active ion-radicals. On the other hand, the poor activity of c.TiO2 for water splitting is related to certain defect-induced inter-band charge trapping states in the close vicinity of valence and conduction bands of c.TiO2, as revealed by thermoluminescence spectroscopy. Further, the dispersion of nanosize gold particles gave rise to augmented activity of both the catalysts, particularly for water splitting. This is explained by the promotional role of Au-0 or Au-0/TiO2 interfacial sites in the adsorption and charge-adsorbate interaction processes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Band-structure; Interfaces; Microstructure; Nanostructures; Semiconductors

Revisiting HOPG superlattices: structure and conductance properties - Patil, Sumati; Kolekar, Sadhu; Deshpande, Aparna (Surface Science, 2017)
Superlattices observed on highly oriented pyrolytic graphite (HOPG) have been studied extensively by scanning tunnelling microscopy (STM). The interest in the study of graphite superlattices has seen a resurgence since the discovery of graphene. Single layer graphene, bilayer graphene, and few layer graphene can now be grown on different substrates. The adherence of graphene to various substrates often leads to a periodic out-of-plane modulation and superlattices due to lattice mismatch. In this paper, we report STM imaging and scanning tunnelling spectroscopy (STS) of different kinds of superlattices on HOPG characterized by a variation in lattice periodicities. Our study also shows evidence of the displacement of the topmost HOPG layer by scanning different areas of the same superlattice. A correlation between the lattice periodicity with its conductance properties is derived. The results of this work are important for understanding the origin of the superlattice structure on HOPG. Investigation of such superlattices may open up possible ways to modify two dimensional electron systems to create materials with tailored electronic properties.